Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.33549/physiolres.933329
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Adaptations in Aged Skeletal Muscle: Effect of Exercise Training

Abstract: The aging process is associated with a decline in mitochondrial functions. Mitochondria dysfunction is involved in initiation and progression of many health problems including neuromuscular, metabolic and cardiovascular diseases. It is well known that endurance exercise improves mitochondrial function, especially in the elderly. However, recent studies have demonstrated that resistance training lead also to substantial increases in mitochondrial function in skeletal muscle. A comprehensive understanding of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 135 publications
0
6
0
Order By: Relevance
“…Besides mitochondrial biogenesis, the control of mitochondrial quantity and quality depends on the integration of coordinated events such as fusion, fission, and mitophagy. Studies have shown that proper mitochondrial dynamics are impaired during aging (Marzetti et al, 2014) and that exercise is an important strategy for counteracting such effects (Marzetti et al, 2014;Ziaaldini, Hosseini, & Fathi, 2017). In this study, RT did not acutely change any of the proteins related to mitochondrial dynamics.…”
Section: Discussionmentioning
confidence: 40%
“…Besides mitochondrial biogenesis, the control of mitochondrial quantity and quality depends on the integration of coordinated events such as fusion, fission, and mitophagy. Studies have shown that proper mitochondrial dynamics are impaired during aging (Marzetti et al, 2014) and that exercise is an important strategy for counteracting such effects (Marzetti et al, 2014;Ziaaldini, Hosseini, & Fathi, 2017). In this study, RT did not acutely change any of the proteins related to mitochondrial dynamics.…”
Section: Discussionmentioning
confidence: 40%
“…7-9 weeks) endurance training adjuvant to T therapy in mice, 93,94 we showed RET coupled to T therapy augmented PGC1-α/Tfam mRNA, mitochondrial CS activity, 2 and protein levels of complex IV (cytochrome c oxidase subunit 85 ) and V (ATP synthase subunit) 85 (not mtDNA copy number). Possible mechanisms include heightened activation of IGF-1/MAPK pathways 87,95 and augmented MRFs mRNA (e.g. Myogenin) 96 during RET, as observed in the T study group, which consequently mediate mitochondrial gene expression.…”
Section: Discussionmentioning
confidence: 95%
“…For instance, it was reported that ageing is associated with decreases in PGC1-α mRNA (a main regulator of mitochondrial biogenesis and oxidative capacity 86 ), OxPhos capacity, mitochondria enzyme activity (e.g. CS), mtDNA content, and increases in oxidative stress, which all result in an impaired mitochondrial function 87 . Crucially, exercise, including RET, is known to induce mitochondrial adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle mitochondria are subject to age‐related remodelling; for instance, ageing is associated with decreases in mitochondrial biogenesis and oxidative capacity 38 and mitochondrial enzyme activity (e.g. CS), resulting in impaired mitochondrial function 39 (especially in individuals older than 80 years suffering from severe muscle loss, chronic diseases, or orthopaedic issues 40 ). Exercise, including HIIT, is well known to induce mitochondrial adaptations.…”
Section: Discussionmentioning
confidence: 99%